Endophytic strategies decoded by genome and transcriptome analysis of Fusarium nematophilum strain NQ8GII4 - Yan, Siyuan; Zhang, Qingchen; Jia, Shuxin; Guo, Miaomiao; Zhang, Qiangqiang; Gu, Peiwen (Frontiers in Microbiology, 2025)
IntroductionFusarium nematophilum strain NQ8GII4 is an endophytic fungus with significant potential for improving growth and disease resistance of alfalfa. However, the molecular mechanisms underlying the symbiotic relationship between NQ8GII4 and alfalfa roots remain poorly understood.MethodsIn this study, we conducted (1) a comparative genomic analysis of selected saprophytic, pathogenic, and endophytic fungi, including molecular phylogeny analysis, whole-genome alignment, and divergence date estimation positioning, and (2) transcriptomic profiling of alfalfa roots infected with NQ8GII4.ResultsOur findings reveal that NQ8GII4 is genetically closely related to F. solani, suggesting it diverged from Fusarium phytopathogens. During the early stages of symbiosis establishment, genes encoding glycosyltransferases (GTs), fungal cell wall-degrading enzymes (FCWDEs), and steroid-14α-demethylase (CYP51) were significantly downregulated, potentially suppressing hyphal growth of the fungus. Once symbiosis was established, NQ8GII4 secreted effectors that activated plant immunity, which in turn could slow growth of the fungus. Moreover, genes involved in secondary metabolite biosynthesis, such as type I polyketide synthases (T1PKS) and non-ribosomal peptide synthetases (NRPSs), were significantly downregulated. Homologs of autophagy-related genes, including ATG1, ATG2, ATG11, and others, were also downregulated, suggesting that reduced phytotoxin production and autophagy inhibition is a consequence of NQ8GII4’s symbiosis.DiscussionThis study investigated the comprehensive molecular and genetic mechanisms governing the interaction between NQ8GII4 and alfalfa roots. Beyond the NQ8GII4-alfalfa system, these findings also provide a valuable molecular framework for understanding the mechanism of interactions between endophytic fungi and their host plants.